OPTIMISASI BIAYA TRANSPORTASI MENGGUNAKAN METODE STEPPING STONE DENGAN SOLUSI AWAL TOCM-SUM APPROACH DAN KSAM - TARIGAN, MIKHA LAYASISA; TASTRAWATI, NI KETUT TARI; UTARI, IDA AYU PUTU ARI (E-Jurnal Matematika; Vol 12 No 1 (2023)DO - 10.24843/MTK.2023.v12.i01.p403, 2023)
Transportation problem is one of the problems that can be solved by using linear programming.  Transportation method allow businessmen to minimize distribution costs, increase profits, and also fulfill the consumer needs at the same times. The transportation method has two stages of completion, namely the initial basic solution and the optimum solution.  The initial basic solution has many developments, two of which are the Total Opportunity Cost Matrix Sum (TOCM-SUM) Approach and the Karagun Sahin Approximation Method (KSAM).  Moreover, the optimal solution has two methods of completion, namely modified distribution and stepping stone. This study will compare two method between TOCM-SUM Approach and KSAM which then optimized by using stepping stone method.On other case, the result of using this two method might produce a different number, where as in this study by using TOCM-SUM Approach method will produce 9 alocation routes, meanwhile using KSAM will produce 10 alocation routes. The results from this study shows that KSAM produced a minimum distribution cost with a difference of Rp114.770,00 from the TOCM-SUM Approach.